REVISITANDO A LITERATURA SOBRE O EMPRESARIADO INDUSTRIAL BRASILEIRO: dilemas e controvérsias - Sousa Barbosa, Agnaldo (Caderno CRH, 2013)
68 barbosa Ao longo das últimas cinco décadas, diferentestradições interpretativas se ocuparam da tarefade buscarexplicar a gênese do empresariado industrial brasileiro eanalisar seu padrão de conduta do ponto de vista doempreendimento econômico e, por outro lado, diante dasprincipaisquestões políticas do país.Não obstanteser esse um tema pulsante, tendo em vista a centralidade do papel a serdesempenhado por esse ator social na urdidura dos fios e tramas doprocesso de modernização capitalista dopaís noséculo XX, seu estudo não é objeto deumaprodução profícua, aocontrário do queacontece, por exemplo, com as investigações sobreaclasse operária. Este trabalho realiza um brevebalançodo que julgamos constituir as mais expressivas dentre asvariáveis possíveis nainterpretação daexperiência de classe do empresariado industrial, reivindicando a complexidade inerente ao temaem contraponto à generalizaçãosimplificadorarecorrente na maioria dos trabalhos sobre o assunto. PALAVRAS-CHAVE: Empresariado industrial. Classe Social. ComportamentoEmpresarial. Industrialização Brasileira. REVISITINGTHE LITERATURE ON BRAZILIANINDUSTRIALISTS: dilemmas and controversies Agnaldo Sousa Barbosa Over the past five decades several different interpretative traditionshave taken on the task of trying to explain the origin ofindustrialists in Brazil and to analyze their behavior pattern from abusiness perspective, as well as in response to the country’sbiggest political issues. Although this is a stimulating subject,considering the important role to be played by these social actors inweaving the fabric of capitalist modernization in 20th century Brazil,not much of substance has been written about it, in contrast with, forinstance, research about the working class. This paper makes a briefassessment of what we believe to be one of the most significant among the possible variables for interpreting theexperience of the industrialist class, which demands the complexityinherent to the topic as a counterpoint to the simplifiedgeneralization which is recurrent in most writings about this subject. KEY WORDS: Industrialists. Social class. Business behavior. Brazilianindustrialization. RELECTUREDES ÉCRITS CONCERNANTLES ENTREPRENEURS INDUSTRIELS BRÉSILIENS: dilemmes etcontroverses Agnaldo Sousa Barbosa Au cours des cinquante dernières années,différentes traditions interprétatives ontcherchéà expliquer la genèse del’entreprenariatbrésilien et à analyser sa manièred’être du point de vue del’entreprise économique, mais aussi face aux questions essentielles de lapolitique nationale. Même s’il s’agitd’unthème excitant étant donnél’importance durôle que doit assumer cet acteur social dansl’élaboration du processus de modernisationcapitaliste dupays au XXe siècle, son étude n’est pasobjetd’une production abondante contrairement à ce quisepasse, par exemple, pour les investigations concernant la classe ouvrière. Cette analyse fait un bilan succinct de ce quenousjugeons être la plus expressive des variables possibles del’interprétation del’expérience de la classedes entrepreneurs industriels qui revendique la complexitéinhérente au thème, en opposition à lagénéralisation simplificatrice habituelle dans laplupartdes travaux effectués sur ce thème. MOTS-CLÉS: entreprenariat industriel; classe sociale;comportement entrepreneurial; industrialisation brésilienne. <small style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255); font-weight: bold;">PublicaçãoOnlinedo Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255); display: inline ! important; float: none; font-weight: bold;"> <small style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255); font-weight: bold;">PublicaçãoOnlinedo Caderno CRH: http://www.cadernocrh.ufba.br